2019
DOI: 10.1096/fj.201802720rr
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A knockdown triggers epithelial‐mesenchymal transition and carcinogenesis features of renal cells: role in renal cell carcinoma

Abstract: Down‐regulation/mutation of AT‐rich interactive domain 1A (ARID1A), a novel tumor suppressor gene, has been reported in various cancers. Nevertheless, its role in renal cell carcinoma (RCC) remained unclear and underinvestigated. We thus evaluated carcinogenesis effects of ARID1A knockdown in nonmalignant Madin‐Darby canine kidney (MDCK) renal cells using small interfering RNA (siRNA) against ARID1A (siARID1A). The siARID1A‐transfected cells had decreased cell death, increased cell proliferation, and cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 65 publications
4
24
1
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) plays an important role in cancer development and progression (18). Somsuan et al found in 2019 that ARId1A knockout promoted EMT in cells, which was characterized by an increased fusiform index and stromal markers, decreased epithelial markers, and enhanced renal cell migration activity and drug resistance (19). Wilson et al in 2019 also indicated that the abnormal endometrial tissue diffusion was closely related to the increase in EMT-related gene expression induced by ARId1A deletion (20).…”
Section: Role Of Arid1a In Epithelial-mesenchymal Transition In Breasmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) plays an important role in cancer development and progression (18). Somsuan et al found in 2019 that ARId1A knockout promoted EMT in cells, which was characterized by an increased fusiform index and stromal markers, decreased epithelial markers, and enhanced renal cell migration activity and drug resistance (19). Wilson et al in 2019 also indicated that the abnormal endometrial tissue diffusion was closely related to the increase in EMT-related gene expression induced by ARId1A deletion (20).…”
Section: Role Of Arid1a In Epithelial-mesenchymal Transition In Breasmentioning
confidence: 99%
“…A wide range of cancer-gene mutations are detected by NGS and loss of function mutations in the ARID1A is detected repeatedly and frequently in various cancer types [13,21]. A recent study revealed that ARID1A knockdown in renal cells led to epithelial-mesenchymaltransition, highlighting its role in cell differentiation and tissue homeostasis [22].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that HDACi not only suppress the EMT but also compromise DNA repair processes of cancer cells [37]. The involvement of EMT was confirmed in another recent paper [38], where they observed that the knockdown of AT-rich interactive domain 1A (ARID1A), a novel tumour suppressor gene, by siRNA both in non-malignant MDCK and malignant 786-O RCC cells, triggers EMT. The down-regulation of ARID1A protein expression was confirmed also in human RCC tissues.…”
Section: Cultured Cellsmentioning
confidence: 59%